Analytical fragility curves for non-skewed highway bridges in Chile. (15th June 2017) - Martínez, A.; Hube, M.A.; Rollins, K.M.
Highlights: Fragility curves are obtained for typical non-skewed highway bridges in Chile. The seismic effect of seismic bars is assessed experimentally. The fragility curves are validated with statistical damage from 2010 Chile earthquake. The transverse seat width in bridges is critical to reduce the probability of collapse. Abstract: Recent earthquakes in Chile and worldwide have caused significant economic losses due to the damage on the road bridge network. To conduct seismic risk assessment studies and to improve resilience of bridges, seismic vulnerability studies are required. The main objective of this study is to construct fragility curves of typical non-skewed highway bridges in Chile. The fragility curves are obtained from an incremental dynamic analysis of a two-dimensional model of the bent cap of a two-span simply supported underpass. As most bridges are constructed with seismic tie-down bars, their constitutive behavior was obtained experimentally. A total of five seismic bar specimens were tested to characterize their cyclic behavior in bridges with and without transverse diaphragms. The incremental dynamic analysis was performed with the two horizontal components of seven seismic records obtained from the Mw 8.8, 2010 Chile earthquake. Additionally, a parametric study is conducted to assess the seismic behavior of bridges with different configurations of seismic bars, with lateral stoppers, and with varying length of the transverse seat width. Results from this study reveal that seismic bars have a limited contribution to the seismic performance of the studied bridge, especially when lateral stoppers are incorporated. Additionally, the transverse seat width is found to be critical to reduce the collapse probability of the superstructure. The provided fragility curves may be used for seismic risk assessment and to evaluate possible improvements in seismic bridge design codes.